2019
DOI: 10.1109/access.2018.2885375
|View full text |Cite
|
Sign up to set email alerts
|

What are the Indonesian Concerns About the Internet of Things (IoT)? Portraying the Profile of the Prospective Market

Abstract: This paper aims to characterize the profile of the prospective IoT market in Indonesia. The primary data were collected in July 2018 through a comprehensive survey that sampled respondents representing the whole Indonesian population. The questionnaire was developed by extracting the 4 (four) main issues regarding which the potential users of the IoT technology may have concerns, i.e., willingness to use the IoT services, concerns related to rejection and worries about the IoT, the characteristics of the IoT h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The result of this study also in line with the research of Suryanegara et al (2018) which showed that the majority of the Indonesian market still has a "psychological dependency" on the old system. Although new technology may serve as a disruptive force causing inevitable changes to the old system, society still values a new technology that merely supports the existing system instead of replacing it.…”
Section: Results Of Hypothesis Testingsupporting
confidence: 87%
“…The result of this study also in line with the research of Suryanegara et al (2018) which showed that the majority of the Indonesian market still has a "psychological dependency" on the old system. Although new technology may serve as a disruptive force causing inevitable changes to the old system, society still values a new technology that merely supports the existing system instead of replacing it.…”
Section: Results Of Hypothesis Testingsupporting
confidence: 87%
“…We further utilize the difference between the two scores to exploit the lessons learned and inform the government as to how it should undertake strategic actions to improve quality. Some previous studies have addressed the case of Indonesian smart cities [6]- [8], and our previous work also presents cases of the IoT and relevant technological implementation in Indonesia [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…The inhabitants are spread over six main island territories, as shown in Fig. 1-the two most densely populated islands are Sumatra (20% of the population) and Java (60% of the population) [3]. Six major MNOs serve Indonesia (Telkomsel, Xl Axiata, Indosat, H3I, STI, and Smartfren).…”
Section: Introductionmentioning
confidence: 99%
“…Six major MNOs serve Indonesia (Telkomsel, Xl Axiata, Indosat, H3I, STI, and Smartfren). [3] In Indonesia, Kominfo (the Ministry of Communication and Information) regulates frequency spectrum allocation licensing. In the past, MNOs have proposed utilizing the frequency spectrum and have applied to the Ministry for permits to utilize the radio frequency spectrum to provide telecommunications services.…”
Section: Introductionmentioning
confidence: 99%